2019
DOI: 10.17977/um009v28i12019p001
|View full text |Cite
|
Sign up to set email alerts
|

Kepemimpinan Kepala Sekolah dalam Penguatan Peran Multi-Stakeholders Forum (Masalah dan Strategi Solutif Peningkatan Mutu SD – SMP Satu Atap di Daerah Terpencil)

Abstract: The study aims to describe the problem and find effective leadership strategies that can be done by principals in Elementary School -Junior High School One Roof (SATAP) in remote areas. Qualitative research with a multi-site approach. The data was obtained through the principal, the head of the LPIKIPI representative (Training Institute and Indonesian Educational Innovation Consultant), and tested the credibility and validity in triangulation through the Forum Group Discussion (FGD) and expert testing. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Dalam bidang pendidikan, kebijakan diberlakukan untuk membangun dunia pendidikan agar menghasilkan pengelolaan pendidikan yang berkualitas dan prospektif (Arifin, Juharyanto, Mustiningsih, & Taufiq, 2018;Juharyanto, Sultoni, Arifin, & Nurabadi, 2019). Kasus di Indonesia, pendidikannya masih stagnan karena proses penyelenggaraannya dianggap tidak mampu menghasilkan output yang baik dan berkualitas.…”
Section: Pendahuluanunclassified
“…Dalam bidang pendidikan, kebijakan diberlakukan untuk membangun dunia pendidikan agar menghasilkan pengelolaan pendidikan yang berkualitas dan prospektif (Arifin, Juharyanto, Mustiningsih, & Taufiq, 2018;Juharyanto, Sultoni, Arifin, & Nurabadi, 2019). Kasus di Indonesia, pendidikannya masih stagnan karena proses penyelenggaraannya dianggap tidak mampu menghasilkan output yang baik dan berkualitas.…”
Section: Pendahuluanunclassified
“…Limited funds budget, educated teachers are not linear with the subjects taught, the support of low society to school activities is a problem for the school head Satap in the disadvantaged area. The problem requires the school principal to be able to portray the role well, as a leader or manager in the school [3], [7], [9]. Seeing the problem in the management of SATAP, can not be removed from the management support factor of the SATAP itself.…”
Section: A Form Of Principal Tips In Managing the Satap School In DImentioning
confidence: 99%
“…Involvement of local community leaders in supporting school efforts to improve school quality is also the principal's concern [7], [8]. How the headmaster can make a persuasive approach with community leaders around the school so that the programs compiled by the one roof school are acceptable and supported by the local community [9]. Therefore, this research seeks to photograph the problem by researching Polewali Mandar and Mamuju West Sulawesi and Bondowoso East Java where there are several one roof schools in the area.…”
Section: Introductionmentioning
confidence: 99%
“…Principal's awareness about the importance of integrating humanistic values will encourage all school stakeholders to remain active in making various innovations in developing a one-stop school (SATAP). Several previous research revealed that high leadership enthusiasm significantly influences the success of principals in developing their schools (Gibson, 2014;Hyson, 2013;Juharyanto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%